Effect of biochar on soil physical and hydrological properties, and on growth, yield, quality of rabi groundnut (Arachis hypogaea L.) in red sandy loam soils of North Coastal Andhra Pradesh: EFFECT OF BIOCHAR ON GROUNDNUT IN RED SANDY LOAM SOILS OF COASTAL ANDHRA PRADESH - P GURUMURTHY; B GOWTHAMI (Journal of Oilseeds Research, 2019)
A field experiment was conducted in red sandy loamsoils of North Coastal Andhra Pradesh to study the effect of biochar on soil physical and hydrological properties, and on growth and yield of rabi groundnut (variety K-6) during 2018-19. Biochar application to soil had significant influence on soil bulk density, porosity and maximum water holding capacity, non-significant influence on final infiltration rate and saturated hydraulic conductivity. Significantly low bulk densities (1.40 mg/m3 and 1.39 mg/m3) and high total porosities (47.17% and 47.55%) of soil at sowing stage were recorded in treatments which received biochar @ 6 t //ha (T5 & T8) and these treatments were on par with treatments which received biochar @ 4 t /ha(T4 and T7) and @ 2 t //ha (T3 and T6). However, T5 and T8 were significantly lower in bulk densities and higher in total porosities when compared to T1 (control) and T2 (100% RDF). Highest bulk density of 1.58 Mg /m3 and lowest total porosity ofsoil (40.38%) was noticed in T1 (control). Soil penetration resistance and soil temperature followed the trend of bulk density. In general, soil bulk density, soil penetration resistance and soil temperature increased fromsowing to harvesting stage of groundnut crop, but the percent pore space decreased. Biochar addition to soil impacted the maximum water holding capacity (MWHC) by recording increased water retention with increased rate of biochar addition from control to 2 t /ha up to 6 t /ha. Biochar addition @ 6 t /ha (T5 & T8) significantly increased MWHC of soil when compared to control (T1) and 100% RDF (T2). A slight but non-significant decrease in final infiltration rate and saturated hydraulic conductivity was noticed by biochar addition. Groundnut crop growth in the form of leaf area index at pod development stage was highest (3.16) in T5 (biochar 6 t /ha + 100% RDF) which was on par with T4 (biochar 4 t/ha + 100% RDF) and both T5 & T4 were significantly higher than T6, T7, T8, T2 and T1. In general, the dry matter accumulation increased from peg penetration to harvest. Highest dry matter accumulation of 2950.90 kg /ha and 6427.54 kg /ha, respectively at peg penetration and pod development stage was observed in T5 (100% RDF + biochar @ 6 t /ha) which was on par with T4 (100% RDF + biochar @ 4 t /ha), T3 (100% RDF + biochar @ 2 t /ha), T8 (75% RDF + biochar @ 6 t /ha) treatments. Groundnut pod yield was highest (4020 kg /ha) in T5 treatment (100% RDF + biochar @ 6 t /ha), which was on par with T4 (100% RDF + biochar @ 4 t /ha) and T8 (75% RDF + biochar @ 6 t /ha). From these observations, it could be concluded that application of biochar at either @ 4 t/ha + 100 % RDF or @ 6 t /ha + 75% RDF, resulted in better soil physical environment and also increased availability of nutrients which resulted in higher plant growth, dry matter production and pod yield in groundnut.